Municipal bankruptcy in the Czech and Slovak Republic (case study) - Hrůza, Filip; Novotná, Sandra (Univerzita Pardubice, 2017)
Municipal sector is an important and integral part of each national public administration structure but sometimes overlooked and neglected. Municipalities perform and execute various tasks and responsibilities according to the residents and its scope differs by each country settings. Financial health of municipalities is thus one of essential questions of their proper functioning and providing public services as well as its own continuous development. Municipal bankruptcy as extreme negative financial situation of municipality is not a new issue but in the Czech and Slovak Republic still underdeveloped and underestimated as well as associated political debate considering introduction of municipal bankruptcy into national legislation. The aim of this paper is to reveal this issue in both countries and identify causes and patterns of financially distressed Czech and Slovak municipalities. In spite of limited research sample this case study of two countries with similar conditions shows some interesting insights and preliminary findings but also questions for further research in this not very developed issue in both countries from the analytical point of view.
Keywords: municipality; bankruptcy; financial distress; public policy; regulation; H12; H72; M48; R51